Beyond Communication Constructing Horenso As An Employee Performance Metric In Indonesia’s Garment Manufactur - Kuswara, Galuh Boga Kuswara; Suryana, Suryana; Rofaida, Rofi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study positions Horenso, which consists of hokoku, renraku, and sodan, as an indicator of employee performance rather than merely an organizational communication pattern in the garment industry. The research was conducted at PT Hini Daiki Indonesia, Tasikmalaya Regency, which has experienced a decline in productivity during the 2024–2025 period. A quantitative approach with a causal design was applied, involving 100 lower management employees selected as respondents. Data were collected using a five-point Likert scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling with the SmartPLS application. The findings indicate that the measurement model demonstrates good validity and reliability, while the structural model shows strong explanatory power. The analysis confirms that Kaizen work culture has a significant effect on Horenso performance, as does work competence, which includes technical, managerial, social, cognitive, and innovative aspects. Furthermore, Kaizen work culture significantly influences morality and spirituality, which in turn enhance Horenso performance. Mediation testing reveals that morality and spirituality play an essential role in channeling the influence of Kaizen work culture and work competence on Horenso performance. These findings emphasize the necessity of synergy between Kaizen, competence enhancement, and the internalization of moral and spiritual values in Horenso practices through reporting, information sharing, and responsive consultation.